Exploring the Impact of Digital Learning Environments on Student Engagement and Academic Performance A Global Perspective - Kumar, Rohan; Wei, Li (PT. Technology Laboratories Indonesia (TechnoLabs), 2024)
This study investigates the impact of digital learning environments on student engagement and academic performance in higher education. Utilizing a mixed-methods approach, the research combines quantitative surveys with qualitative interviews to explore how digital tools influence learning experiences. A survey of 300 students revealed a significant positive correlation between digital tool usage and student engagement levels, with 78% of respondents indicating that these tools enhanced their learning experience. In-depth interviews with 20 educators highlighted the benefits of technology in fostering collaboration and community, while also noting challenges related to access and digital literacy. The study concludes that while digital learning environments enhance educational outcomes, addressing disparities in access and providing training for educators is crucial for maximizing their effectiveness. Future research should focus on long-term impacts and strategies to ensure equitable access to digital resources.